The Implementation of Teams Games Tournament (TGT) Model on Increase Students’ Outcomes Learning at SMKN 2 Banda Aceh - Dasuki Dasuki (Asian Journal of Science Education, 2021)
The purpose of this study was to determine the application of new theories regarding the application of the Teams Games Tournament (TGT) model in studying environmental concepts in the implementation of building construction whether or not it can increase the outcomes learning of students in class XI-TKGSP SMK Negeri 2 Banda Aceh or not. The subjects of this study were students of class XI TKGSP SMK Negeri 2 Banda Aceh, totaling 25 students consisting of 2 women and 23 men. The research procedure is planning, action, observation, and reflection. The results showed that the application of learning with the Teams Games Tournament (TGT) model can increase students' outcomes learning. This is indicated by the results in the first cycle of meeting 1 the average value of the cognitive aspect is 6.64, the psychomotor aspect is 6.48, and the affective aspect is C with a classically complete score obtained only 28%. In the second meeting, the average value of cognitive aspects was 6.96, psychomotor was 6.8, and affective aspects were C with a learning completeness score of 44%. Cycle II meeting 1 cognitive aspect 7.36, psychomotor aspect 7.12, and affective aspect B with a complete learning score of 64%. The second meeting of cognitive aspects 7.6, psychomotor aspects 7.28, and affective aspects B with a classically complete score obtained by 76%. Learning runs very interactively and can be used as a reference for teachers to be implemented in the classroom so that the learning atmosphere is more fun.